Unravelling the eco-specificity and pathophysiological properties of Cutibacterium species in the light of recent taxonomic changes. (October 2021) - Dekio, Itaru; Asahina, Akihiko; Shah, Haroun N.
Abstract: In 2016, a new species name Cutibacterium acnes was coined for the well-documented species, Propionibacterium acnes, one of the most successful and clinically important skin commensals. The nomenclatural changes were brought about through creation of the genus Cutibacterium, when a group of propionibacteria isolates from the skin were transferred from the genus Propionibacterium and placed in the phylum Actinobacteria . Almost simultaneously, the discovery of two novel species of Cutibacterium occurred and the proposal of three subspecies of C. acnes were reported. These dramatic changes that occurred in a long-established taxon made it challenging for the non-specialist to correlate the huge volume of hitherto published work with current findings. In this review, we aim to correlate the eco-specificity and pathophysiological properties of these newly circumscribed taxa. We envisage that this information will shed light on the pathogenic potential of new isolates and enable better assessment of their clinical importance in the foreseeable future. Currently, five species are recognized within the genus: Cutibacterium acnes, Cutibacterium avidum, Cutibacterium granulosum, Cutibacterium modestum (previously, " Propionibacterium humerusii "), and Cutibacterium namnetense . These reside in different niches reflecting their uniqueness in their genetic makeup. Their pathogenicity includes acne inflammation, sarcoidosis, progressive macular hypomelanosis, prostate cancer, and infections (bone, lumbar disc, and heart). This is also the case for the three newly described subspecies of C. acnes, which are C. acnes subspecies acnes ( C. acnes type I), subspecies defendens ( C. acnes type II), and subspecies elongatum ( C. acnes type III). C. acnes subspecies acnes is related to inflamed acne and sarcoidosis, while subspecies defendens to prostate cancer and subspecies elongatum to progressive macular hypomelanosis. Because the current nomenclature is based upon polyphasic analyses of the biochemical and pathogenic characteristics and comparative genomics, it provides a sound basis studying the pathophysiological roles of these species. Graphical abstract: Image 1 Highlights: Genus Cutibacterium was created when genus Propionibacterium was reclassified into four genera. The genus consists of five species including two new species, C. modestum and C. namnetense. These species differ in their niche and pathogenicity in humans. C. acnes consists of three subspecies, which also differ in their niche and pathogenicity.